PLANT FORMING OF GENERAL CULTURE OF STUDENTS OF STOMATOLOGY FACULTY OF IVANO-FRANCIVS’K NATIONAL MEDICAL UNIVERSITY - Бугерчук, О. В.; Бульбук, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the article the questions is under consideration into question, related to the features of education of students of stomatology faculty of medical university. Authors show actuality of conducting of educate measures with students, efficiency of work of counsels of groups of students and feature of conducting of educate measures.